Menghitung Kecepatan Membaca Arab Melayu Dalam Cerita “Orang Batak Menyetop Taksi” Kelas 2021 A - Hasnah Faizah; Eka Dilla Pahri; Fitri Auliya Rahmi; Hanna Catrina Hutapea; Mayang Marisya; Mita An-nisa Surya. F; Rinita Sinaga (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to assess the reading speed levels of students. The sample for this study consists of students from the 2021 A class of the Indonesian Language and Literature Education Program, Faculty of Education, Universitas Riau. The data analysis technique employed is the test method, with quantitative data analysis techniques used to analyze the results of a fast reading test in Arabic Malay texts. The data analysis procedure involves measuring the reading speed of students when reading Arabic Malay texts. The research findings indicate that the reading speed of the 2021 A class students is approximately 54.08 words per minute (wpm). This figure suggests that the students' reading speed is below the established standard for reading speed in the context of Arabic Malay texts, which is 200 wpm. The conclusion drawn from this research is that students tend to read at a slower pace, possibly as an effort to reduce reading errors, resulting in their reading speed falling below the expected standard.